(untitled) (Antropolítica - Revista Contemporânea de Antropologia, 2014)
This lecture discusses the relationship between two academic disciplines, law and anthropology, and suggests that the optimal relationship is, on the one hand, competitive and conflictual, and on the other hand, mutually respectful and supportive - something like the relationship between two sibling rivals. The conflictual aspects of this relationship derive from the different orientations of the two fields - instrumental for law, speculative for anthropology - and the fact that anthropology, based on long-term ethnography, often challenges and subverts law’s claims to distinctive authority.The positive aspects of the relationship build on the possibilities that each field can genuinely assist the other, as anthropological understanding can be extremely useful to lawyers, while lawyers are often the legal system’s most astute observers and critics, and thus can provide anthropologists with invaluable insights into the actual operations of legal systems. These points are illustrated through references to the author’s fieldwork in Palestine and legal practice experience in the United States.